Ethics of multiple citizenship - Tanasoca, Ana (New York Cambridge, 2018)
"Citizenship is no longer an exclusive relationship. Many people today are citizens of multiple countries, whether by birth, naturalization, or even through monetary means, with schemes fast-tracking citizenship applications from foreigners making large investments in the state. Moral problems surround each of those ways of acquiring a second citizenship, while retaining one's original citizenship. Multiple citizenship can also have morally problematic consequences for the coherence of collective decisions, for the constitution of the demos, and for global inequality. The phenomenon of multiple citizenship and its ramifications remains understudied, despite its magnitude and political importance. In this innovative book, Ana Tanasoca explores these issues and shows how they could be avoided by unbundling the rights that currently come with citizenship and allocating them separately. It will appeal to scholars and students of normative political theory, citizenship, global justice, and migration in political science, law, and sociology"--
Machine generated contents note: Acknowledgements; 1. Introduction; Part I. Acquisition: 2. Multiple Citizenship by Birthright; 3. Multiple Citizenship by Naturalization; 4. Multiple Citizenship by Investment; Part II Consequences: 5. Multiple Citizenship and Collective Decision-making; 6. Multiple Citizenship and the Boundary Problem; 7. Taxing Multiple Citizens and Global Inequality; 8. Conclusions; References; Index.
Originally presented as the author's thesis (doctoral)--University of Essex, 2015.
Includes bibliographical references (pages 178-196) and index.
Keywords: Dual nationality; Citizenship; Conflict of laws